2020
DOI: 10.3390/rs12142311
|View full text |Cite
|
Sign up to set email alerts
|

Structure from Motion of Multi-Angle RPAS Imagery Complements Larger-Scale Airborne Lidar Data for Cost-Effective Snow Monitoring in Mountain Forests

Abstract: Snowmelt from mountain forests is critically important for water resources and hydropower generation. More than 75% of surface water supply originates as snowmelt in mountainous regions, such as the western U.S. Remote sensing has the potential to measure snowpack in these areas accurately. In this research, we combine light detection and ranging (lidar) from crewed aircraft (currently, the most reliable way of measuring snow depth in mountain forests) and structure from motion (SfM) remotely piloted aircraft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…However, diverging results at the experimental plots in Laret and Sodanklyä imply that such parametrizations would need to account for climatic conditions as well. Future studies could combine spatially distributed forest snow datasets from repeated lidar flights (Broxton & van Leeuwen, 2020; Painter et al., 2016; Pflug & Lundquist, 2020) and hyper‐resolution models to develop dedicated snow‐covered fraction parametrizations for forested areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, diverging results at the experimental plots in Laret and Sodanklyä imply that such parametrizations would need to account for climatic conditions as well. Future studies could combine spatially distributed forest snow datasets from repeated lidar flights (Broxton & van Leeuwen, 2020; Painter et al., 2016; Pflug & Lundquist, 2020) and hyper‐resolution models to develop dedicated snow‐covered fraction parametrizations for forested areas.…”
Section: Discussionmentioning
confidence: 99%
“…Broxton and van Leeuwen quite recently reported an approach combining airborne LiDAR data from a similar platform as Painter et al with structure from motion (SfM) data measured from a UAV over the same plot. 11 They could demonstrate that airborne LiDAR outperforms SfM in densely forested regions, whereas in sparsely forested areas both methods give comparable results. Since this is no real surprise, the more important finding is rather that they found a relationship between a small scale SfM map and a previous LiDAR data set over a larger area.…”
Section: Remote Sensing Of Snow Depthmentioning
confidence: 99%
“…This is already a huge advantage of LiDAR itself over other techniques such as SfM because it allows for precise snow height mapping even under conditions like a canopy covering the ground. 8,11,12 This advantage of full-waveform recording is illustrated in the panel on the right. The full-waveform signal provides additional information on parameters like canopy height or structure.…”
Section: Technical Realizationmentioning
confidence: 99%
“…In the paper [1], the authors carried out an interesting combination of UAV Photogrammetry and Large-Scale Airborne Lidar Data to monitor snow masses in a forested region in central Arizona, United States. They observed that in low dense forest conditions, both sources of data deliver similar snow depth maps while in high dense forest, lidar maps are more accurate.…”
Section: Overview Of Contributionsmentioning
confidence: 99%